1999
DOI: 10.1139/a99-009
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the potential hazards of environmental selenium for Canadian water birds

Abstract: Elevated dietary intake of selenium (Se) causes dramatic teratogenic and other reproductive effects in water birds at dietary levels only a few times greater than those that are generally regarded as nutritionally essential. Possible risks to the health of Canadian water birds and other wildlife from Se may be posed by seleniferous habitats in western Canadian provinces, and over-wintering by migratory water birds in some National Wildlife Refuges in the western U.S.A. where Se-related deaths and embryonic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Presumably, birds are protected against Hg toxicity but this result raises concern about the surplus of Se and its possible toxicity. Hepatic Se concentrations exceeding 10 µg g -1 dw were associated with lower reproductive success in breeding female mallards (Heinz et al, 1987;Outridge et al, 1999;Stanley et al, 1996). It is remarkable that this element was highly accumulated in female dunlins and redshanks compared to males, as previously observed in American avocets Recurvirostra americana from the San Francisco Bay (Ackerman and Eagles-Smith, 2009).…”
Section: Trace Element Bioaccumulation In Shorebird Speciessupporting
confidence: 59%
See 1 more Smart Citation
“…Presumably, birds are protected against Hg toxicity but this result raises concern about the surplus of Se and its possible toxicity. Hepatic Se concentrations exceeding 10 µg g -1 dw were associated with lower reproductive success in breeding female mallards (Heinz et al, 1987;Outridge et al, 1999;Stanley et al, 1996). It is remarkable that this element was highly accumulated in female dunlins and redshanks compared to males, as previously observed in American avocets Recurvirostra americana from the San Francisco Bay (Ackerman and Eagles-Smith, 2009).…”
Section: Trace Element Bioaccumulation In Shorebird Speciessupporting
confidence: 59%
“…This study demonstrated that shorebirds using the same habitats in the Pertuis Charentais were characterized by differential trace element bioaccumulation. Concentrations of As and Se tend to be elevated in red knots and dunlins and possibly could trigger adverse effects in these species (Heinz et al, 1987;Kunito et al, 2008;Outridge et al, 1999;Stanley et al, 1996). Redshanks displayed however higher Cd concentrations in internal tissues.…”
Section: Relationship Between Trophic Position Feeding Habitat and Tmentioning
confidence: 99%
“…Se has the property to react with thiols which generate reactive oxygen species (Spallholz and Hoffman, 2002). Based on a review of the literature, Outridge et al (1999) suggested that hepatic Se concentrations > 10 µg g -1 dw are associated with reduced adult weight gain, lower reproductive success in breeding female and increased teratogenesis in their offspring. Moreover, Se concentrations exceeded 33 µg g -1 dw could be considered harmful to the health of birds (Heinz, 1996).…”
Section: Toxicity Significancementioning
confidence: 99%
“…Mine-influenced water (MIW) contains constituents, such as selenium and sulphate, at levels that are potentially toxic to aquatic life [1][2][3] and needs to be treated before discharging to the receiving environment. One cost-effective method for remediating MIW is to use sub-surface flow constructed wetlands, commonly called biochemical reactors (BCRs), that contain waste organic material such as wood-chips, straw, hay, leaf compost, pulp mill biosolids, etc.…”
Section: Introductionmentioning
confidence: 99%